Emerging role of non-coding RNAs in resistance to platinum-based anti-cancer agents in lung cancer - Mondal, Priya; Meeran, Syed Musthapa (Frontiers in Pharmacology, 2023)
Platinum-based drugs are the first line of therapeutics against many cancers, including lung cancer. Lung cancer is one of the leading causes of cancer-related death worldwide. Platinum-based agents target DNA and prevent replication, and transcription, leading to the inhibition of cell proliferation followed by cellular apoptosis. About twenty-three platinum-based drugs are under different stages of clinical trials, among cisplatin, carboplatin, and oxaliplatin are widely used for the treatment of various cancers. Among them, cisplatin is the most commonly used drug for cancer therapy, which binds with RNA, and hinders the cellular RNA process. However, long-term use of platinum-based drugs can cause different side effects and has been shown to develop chemoresistance, leading to poor clinical outcomes. Chemoresistance became an important challenge for cancer treatment. Platinum-based chemoresistance occurs due to the influence of intrinsic factors such as overexpression of multidrug resistance proteins, advancement of DNA repair mechanism, degradation, and deactivation of intracellular thiols. Recently, epigenetic modifications, especially non-coding RNAs (ncRNAs) mediated gene regulation, grasp the attention for reversing the sensitivity of platinum-based drugs due to their reversible nature without altering genome sequence. ncRNAs can also modulate the intrinsic and non-intrinsic mechanisms of resistance in lung cancer cells. Therefore, targeting ncRNAs could be an effective approach for developing novel therapeutics to overcome lung cancer chemoresistance. The current review article has discussed the role of ncRNA in chemoresistance and its underlying molecular mechanisms in human lung cancer.